MODEL INTEGRASI STUDI ISLAM: SAINS DAN BUDAYA NUSANTARA DI PESANTREN KHOLAF - Salman Al Farisi (Jurnal Penelitian Agama, 2018)
Abstract: Modern Islamic boarding schools are also called pesantren kholaf (modern) as acronyms of salaf or ashriyah. The model of integration of Islam, science and culture is contained in the conditions of the Islamic boarding school, the methods, traditions and intellectual spirit of the santri in the pesantren Khalaf with all the combination of Islamic values ​​and culture, having challenges that must be overcome in facing challenges in the global era. With its very integrated the slogan, al muhafadhah 'ala al qadim al shalih wa al-ahdz bi al-jadid allashlah (holding good old things and taking new things better. This slogan can be the key to reconciling tradition and modernization: Modernization in Islamic education is a renewal that occurs in Islamic boarding schools, at least it can erase the image of some people who consider Islamic boarding schools to be traditional educational institutions, now they want to produce true scientists who are able to produce ulama. protect the people and advance the nation and state. Keywords: integration, Islamic studies, Science, Nusantara Culture, and Pesantren Kholaf.